Evidence of Tolerance to Silica-Based Desiccant Dusts in a Pyrethroid-Resistant Strain of Cimex lectularius (Hemiptera: Cimicidae) - David G. Lilly; Cameron E. Webb; Stephen L. Doggett (Insects, 2016)
Insecticide resistance in bed bugs (Cimex lectularius and Cimex hemipterus) has become widespread, which has necessitated the development of new IPM (Integrated Pest Management) strategies and products for the eradication of infestations. Two promising options are the diatomaceous earth and silica gel-based desiccant dusts, both of which induce dehydration and eventual death upon bed bugs exposed to these products. However, the impact of underlying mechanisms that confer resistance to insecticides, such as cuticle thickening, on the performance of these dusts has yet to be determined. In the present study, two desiccant dusts, CimeXa Insecticide Dust (silica gel) and Bed Bug Killer Powder (diatomaceous earth) were evaluated against two strains of C. lectularius; one highly pyrethroid-resistant and one insecticide-susceptible. Label-rate doses of both products produced 100% mortality in both strains, albeit over dissimilar time-frames (3–4 days with CimeXa vs. 14 days with Bed Bug Killer). Sub-label rate exposure to CimeXa indicated that the pyrethroid-resistant strain possessed a degree of tolerance to this product, surviving 50% longer than the susceptible strain. This is the first study to suggest that mechanisms conferring resistance to pyrethroids, such as cuticular thickening, may have potential secondary impacts on non-synthetic insecticides, including desiccant dusts, which target the bed bug’s cuticle.